Procedures For Submitting a Judicial Appeal Before the Administrative Judiciary in The Kurdistan Region of Iraq: A comparative analytical study - Fawaz Khalaf Zahir; Jumha Qadir Salih (QALAAI ZANIST JOURNAL, 2022)
The administrative judiciary is the specialist that promises to monitor the work of the administration in the countries that adopt the dual justice system, and Iraq as one of these countries. The legislator in the Kurdistan Region has followed the administration of the administrative judiciary as the Iraqi legislator followed at the federal level, and this matter certainly requires the presence of an organization It shows the work of this important and vital judiciary, by indicating the bodies that exercise the function of the administrative judiciary, as well as stating the conditions for submitting the judicial appeal before these bodies, and what are their procedures when considering cases that fall within their jurisdiction, in comparison with what the Iraqi legislator followed at the federal level with regard Organizing the administrative judiciary.